ALTERING THE MARKING OF THE REVERSE POSTERIOR INTEROSSEOUS ARTERY FLAP - Fahad Hanif Khan (JPRAS Open, 2022)
ABSTRACT: Background: Full-thickness defects on the dorsum of the hand requires thin, soft, and pliable skin for which there are limited locoregional flaps. The reverse posterior interosseous artery (PIA) flap based on the communicating artery fulfills all above requirements and can reach upto the fingers. However, there has been discrepancy in the surface marking of the flap and the anatomical position of the vessel pedicle. We share our alteration with the marking and ease of harvesting this flap. Method and material: This is a prospective study conducted at a private teaching hospital in Karachi, over a period of 2 years from November 2017 to December 2019. After taking consent and ensuring confidentiality of all patients who had PIA flap reconstruction, we collected patient's demographic details, mode of injury, and flap surface area. We altered the described skin marking and took measures to prevent venous congestion and noted the outcomes in term of flap congestion and flap loss. Results: Twenty-eight patients with a mode age of 32 years were operated during this period. The majority (64.2%) had a motor vehicle accident and machine injuries. The mean surface area of flaps was 6 × 10 cm2, and 11 (39.2%) flaps had venous supercharging. All patients had a 10-20° wrist extension splint for 2 weeks. The mean follow-up of the patients was 14 ± 5 days, and 6 (21.4%) flaps developed a minimal marginal flap loss, which was managed conservatively. Conclusion: By minimally altering our surface marking, we experienced a easy and quick harvesting of this flap. However, one has to be vigilant and take all described precautions for venous congestion.